2014
DOI: 10.1002/dmrr.2513
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of type 2 diabetes mellitus: is it feasible?

Abstract: The increasing global prevalence of type 2 diabetes mellitus (T2DM) requires the implementation of preventive strategies to halt this trend, tailored to the specific needs of individual regions. Risk factors for T2DM are among the main targets for improving health outcomes and curbing the development of diabetes; excessive weight and obesity are two of the most important risk factors that need to be addressed. A growing body of evidence suggests that subjects with pre-diabetes who lose body weight and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
1
25
0
2
Order By: Relevance
“…In addition to ectopic fat accumulation, inflammation and ER stress, recent research findings revealed that gut microbiota plays an important role in the development of obesity and insulin resistance (Lee and Mazmanian, 2010;Ley et al, 2005;Palermo et al, 2014). Indeed, by comparing microbiota from lean and obese patients, Ley and coworkers found that gut microbiota differs in composition (Ley et al, 2006).…”
Section: Role Of Gut Microbiota In the Development Of Insulin Resistancementioning
confidence: 99%
“…In addition to ectopic fat accumulation, inflammation and ER stress, recent research findings revealed that gut microbiota plays an important role in the development of obesity and insulin resistance (Lee and Mazmanian, 2010;Ley et al, 2005;Palermo et al, 2014). Indeed, by comparing microbiota from lean and obese patients, Ley and coworkers found that gut microbiota differs in composition (Ley et al, 2006).…”
Section: Role Of Gut Microbiota In the Development Of Insulin Resistancementioning
confidence: 99%
“…During the last 3 decades, the number of adults with diabetes has doubled, rising from 153 million in 1980 to ;366 million in 2011 (2,3). T2DM is associated with hyperglycemia, which results from insulin resistance mainly in peripheral tissues (4).…”
mentioning
confidence: 99%
“…Besides, insulin resistance in adipocytes, hepatocytes, and muscle cells is still complicating issue. In this context, animal studies provided evidence that RSV as a natural compound has beneficial effects on both mechanisms in these tissues and pancreatic β‐cells (Jiang et al., 2013; Palermo, Maggi, Maurizi, Pozzilli, & Buzzetti, 2014). Although the effects of resveratrol on the inflammatory responses have been investigated in different models, this function of resveratrol in skeletal muscle cells remains unknown.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%